(untitled) (Fiep Bulletin - online, 2010)
The acquisition of healthy lifestyles should be trained from childhood, thus requiring an effort of the agents of socialization that are in first place in the lives of children in order to reverse the sedentary trend. Physical Education (PE), besides being a scientific discipline area that breaks with the traditional paradigms of teaching and learning, the teacher becomes a social agent who leads the protection and promotion of health among its students, giving meaning to the process training, where it reaches its highest development, and being here is the time to prepare and therefore, education, and their claim is to master what they learn and reflect on similar experiences. So that the PE is in human experience its most clear objective, where everyone learns a set of values, attitudes and skills necessary for life in society, from which life styles are considered a durable and incorporated provisions on the subject with implications for the quality of life.